Investigating the migration of pollutants at Barreiro area, Minas Gerais State, Brazil, by the 210Pb chronological method - Bonotto, D. M. [UNESP] (2019)
Barreiro area at Araxá city, Minas Gerais State, Brazil, has been subjected to intense debate because of environmental pollution related to intense mining activities developed for the phosphate and niobium exploitation. Anthropogenic inputs involving the barium release into waters occurred there by the early 1980s because of a leakage occurring at one tailings dam as the adoption of synthetic membrane for the dam waterproofing only started in 2006. This paper reports a novel (radio)chemical record obtained from the analysis of samples of waters and a 35-cm depth sediment core with the aim of focusing the major pathways for the constituents transport there, which are accompanied by information on possible modifications along the time as provided by the use of the 210Pb chronological method. All waters are reducing, despite the rainwater is acid and the remaining (surface water and groundwater) are alkaline. Calcium dominates the rainwater composition, whereas Si is a relevant constituent in the surface and groundwater samples. The sediments are classified as silty sand and sand, Fe2O3 is the major oxide of all sediments sections, reaching a mean concentration value of 47% and it is followed by Organic Matter > BaO > SiO2 > P2O5 > Al2O3 > TiO2 > SO3 > CaO > Nb2O5 whose mean concentration is between 2 and 15%. The Ba levels in waters and sediments from Barreiro area are high, unlike in other streams draining the Araxá municipality. Chloride exhibited a high mobility index, confirming its conservative behavior in solution, whereas the quite low value for iron corroborates that Fe oxides/hydroxides are highly sorptive materials. The CRS 210Pb chronological model allowed identify BaO, Nb2O5, SO3, ThO2 and REEs (La, Ce) concentration peaks around 1973, agreeing with the significant correlations found among these parameters.